Does the Mode of Financing the Budget deficit Matter for Inflation? The Case of the Gambia - Sannoh, Musa; Fanneh, Momodou Mustapha (Technium Social Sciences Journal, 2022)
This study examines whether the mode of financing budget deficit matter for inflation, the case of the Gambia. We are able to identify five instruments that are used for budget deficit financing in the Gambia namely: broad money growth, gross capital formation, official exchange rate and current account balance. We excluded donor fund because it is not a reliable sources of government revenue. The study employed Vector Error Correction Model and Granger Causality to determine the short-run, long-run and causality relationships of the variables respectively. We are able to ascertain that all the selected mode of budget deficit financing adapted by The Gambia have both short-run and long-run Significant impact on Inflation rate between 1970-2020. Notably, broad money growth that is considered to be influenced by state printing of money or the money market is the key mode of budget deficit financing in The Gambia and has high significant impact on Inflation.